Efektifitas Media Online yang digunakan dalam Proses Pembelajaran Daring - Aziz Kurniawan (LP2M STIT Palapa Nusantara, 2021)
The covid-19 pandemic era forced teachers and educators to apply learning by applying online models. Many platforms are offered to facilitate learning, of course it confuses what application is suitable to use so that learning continues to run well even with the online system. So the purpose of this study is (1) to know the understanding and interest of students after learning by using online media platform, (2) to know the effectiveness of the platform that is often used during emergencies Covid-19, (3) able to implement a suitable platform for learning during pandemic Covid-19. This study uses a descriptive qualitative method. where in research the data obtained is then interpreted by the researcher. Based on the results obtained that the use of WAG as a single medium in learning is less effective, while the use of the classroom can be said to be effective because it is applied to students become more active in learning while the google meet application provides effective results in learning because learners are able to directly understand the material brought but has some constraints faced especially in signals and quotas. So it is necessary to use a combination of teleconference applications such as google meet and applications such as WAG / Classroom as a discussion container